A palaeopathological appraisal of pre- and post-European contact societies in northern Zimbabwe - Swanepoel, Elaine; Steyn, Maryna (Southern African Humanities, 2021)
Living conditions and health in Zimbabwe were influenced by Europeans from the 1650s onwards, when the first Portuguese settlers arrived. In this paper, skeletons from three archaeological sites from northern Zimbabwe were investigated to compare the health status of pre- and post-European contact groups. Two sites, Monk’s Kop and Ashford Farms, date from a period prior to European contact. The third, Dambarare, is a post-contact site and includes both Africans and Europeans. The remains assessed in this study were commingled, with a combined minimum number of 90 individuals. At Monk’s Kop (n=43), 14% of individuals presented with signs of skeletal pathology, while 43% of the Ashford Farms individuals (n=7) showed conditions that affect the skeleton. At Dambarare (n=40; both Africans and Europeans), 43% of the Africans and 64% of the Europeans had visible signs of skeletal pathology. Common non-specific conditions included enamel hypoplasia and sub-periosteal bone deposition. Infectious diseases and trauma apparently did not significantly impact on either of the groups. Although not significantly, the pre-European contact populations seem to have suffered less (18% combined average) from pathological conditions than the Dambarare individuals of African ancestry. The individuals in the European sub-sample presented with the most signs of disease. Unfortunately, small sample sizes limited the conclusions that could be made.